2021
DOI: 10.3332/ecancer.2021.1229
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cancer incidence and pattern between urban and rural Nepal: one-year experience from two population-based cancer registries

Abstract: Variations in cancer incidence, mortality and pattern exist in rural and urban areas. Understanding these differences helps in developing targeted cancer prevention and control strategies. However, no previous studies have explored the differences in cancer demographics between the rural and urban areas of Nepal. The data of Kathmandu Valley (urban area) Population-Based Cancer Registry (PBCR) and Rukum (rural area) PBCR were analysed to identify the differences in cancer pattern in rural and urban areas.The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…We observed a significant difference in the standardised rate ratios for the site-specific cancers for rural and urban patients. Similar observations have been reported from previous cancer registries of India, Nepal, China, and the United States (US) [ 14 , 19 , 33 , 40 ]. The significantly higher AAR for liver cancer in rural patients can be partially attributed to a greater prevalence of alcohol use in the rural Indian population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed a significant difference in the standardised rate ratios for the site-specific cancers for rural and urban patients. Similar observations have been reported from previous cancer registries of India, Nepal, China, and the United States (US) [ 14 , 19 , 33 , 40 ]. The significantly higher AAR for liver cancer in rural patients can be partially attributed to a greater prevalence of alcohol use in the rural Indian population.…”
Section: Discussionsupporting
confidence: 90%
“…Another study noted that the AAIR in urban Punjab PBCRs (Chandigarh and SAS Nagar) is almost twice that in rural PBCRs (Mansa and Sangrur) [ 19 ]. Similar trends are observed in Nepal, where the urban (Kathmandu) registry showed 1.6 times higher AAR among males and 1.9 times higher AAR among females in comparison to the rural (Rukum) registry [ 33 ]. Conversely, a study in China revealed significantly higher AAIR in rural men, primarily attributed to oesophageal cancer [ 14 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The coverage of cervical cancer screening in Nepal is only 2.4%. The estimated coverage of cervical cancer screening in rural and urban Nepal is 2% and 4.7% respectively [13], [14]. While the national guidelines of screening for cervical cancer have prioritized VIA as the prime screening method at all levels of health care settings but still it has not been made easily accessible and has not intervened effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring epidemiological trends in cancer through population-based cancer registries (PBCR) is important for cancer control, as it allows for the evaluation of the effectiveness of cancer screening programmes and the assessment of inequalities in cancer treatment, and supports the planning of cancer care services (Parkin 2008). In 2018, PBCR was introduced in Nepal in some districts, and although it was recently expanded, it still covers only 20% of the population (Gyawali et al 2020;Subedi et al 2020Subedi et al , 2021. The lack of a robust PBCR hinders not only the ability to assess cancer incidence and the impact of cancer in the country, but also makes the development of cancer management initiatives more difficult.…”
Section: Introductionmentioning
confidence: 99%